Profil penderita Chronic Kidney Disease (CKD) stadium 5 yang menjalani hemodialisis reguler di Rumah Sakit Umum Daerah (RSUD) Klungkung, Bali, Indonesia - Dewa Ayu Sri Agung Suandewi; I Gede Restu Mahendra Sugiarta; Nyoman Tri Astawa; I Putu Ekariawan (Intisari Sains Medis, 2020)
Background: Chronic Kidney Disease (CKD) is one of the chronic diseases which becomes a major public health problem in Indonesia. The proportion of CKD patient that underwent hemodialysis in Indonesia and Bali in 2018 was 19,3% and 38,7%. This study aims to determine the sociodemographic and clinical profile of patients with CKD stage 5 who underwent regular hemodialysis at Klungkung District General Hospital in 2019. Method: A retrospective cross-sectional study was conducted among 77 samples in the hemodialysis unit of Klungkung District General Hospital by using secondary data obtained from medical records by the total sampling method. The inclusion criteria were patients with CKD stage 5, who underwent regular hemodialysis. The variables evaluated in this study were age, level of education, work status, marriage status, HD period, etiology, vascular access, HBsAg, and level of hemoglobin. Data were analyzed by SPSS version 21 for Windows.Result: The proportion of patient with CKD stage 5 who underwent hemodialysis was 51 to 60 years (33.8%), male gender patients (63.6%), senior high school education (42.9%), working (59.7%), married (93.5%), the duration of year that underwent hemodialysis between 1 to 5 years (85.7%), the most common etiology is chronic pyelonephritis (32.5%), with AV Shunt as vascular access (63.6%), HBsAg test was negative (96.1%), and Hb levels > 10 g/dL (54.5%).Conclusion: Most patients with CKD stage 5 who underwent hemodialysis at Klungkung District General Hospital are male patients, middle age, secondary education level, dominant is working and married, with the first year undergoing hemodialysis 1-5 years. The most common cause of CKD is chronic pyelonephritis in males and hypertension in females. Latar Belakang: Chronic Kidney Disease (CKD) merupakan salah satu penyakit kronis terbanyak yang menjadi masalah kesehatan masyarakat di Indonesia. Angka proporsi penderita CKD yang menjalani hemodialisis di Indonesia dan di Bali tahun 2018 adalah 19,3% dan 38,7%. Penelitian ini bertujuan untuk mengetahui profil sosiodemografi dan klinis penderita CKD stadium 5 yang menjalani hemodialisis reguler di RSUD Klungkung tahun 2019.Metode: Penelitian retrospektif potong lintang dilakukan terhadap 77 sampel di unit hemodialisis Rumah Sakit Umum Daerah Klungkung dengan menggunakan data sekunder yang diperoleh dari catatan medis dengan metode total sampling. Kriteria inklusi adalah pasien dengan CKD stadium 5 yang menjalani hemodialisis reguler. Variabel yang dievaluasi dalam penelitian ini adalah usia, tingkat pendidikan, status pekerjaan, status pernikahan, masa HD, etiologi, akses vaskular, HBsAg, dan kadar hemoglobin. Data dianalisis oleh SPSS versi 21 untuk Windows.Hasil: Proporsi penderita CKD stadium 5 yang menjalani hemodialisis umumnya berada pada rentang umur 51 s/d 60 tahun (33,8%), dengan jenis kelamin penderita terbanyak laki-laki (63,6%), pendidikan SMA (42,9%), bekerja (59,7%), menikah (93,5%), durasi tahun menjalani hemodialisis antara 1 s/d 5 tahun (85,7%), etiologi yang umum ditemui adalah pielonefritis kronis (32,5%), dengan akses vaskular AV Shunt (63,6%), tes HbsAg umumnya negatif (96,1%), dan kadar Hb > 10 gram/dL (54,5%).Simpulan: Sebagian besar penderita CKD stadium 5 yang menjalani hemodialisis di RSUD Klungkung adalah penderita laki – laki, umur pertengahan, tingkat pendidikan menengah, dominan sudah bekerja dan sudah menikah, dengan tahun pertama menjalani hemodialisis 1-5 tahun. Penyebab paling umum dari CKD adalah pielonefritis kronis pada pria dan hipertensi pada wanita.